Estimation of the Genetic Parameters of the Growth Characteristics in Rice crop (Oryza sativa L.) by Effect of Two Methods Irrigation (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Field experiments were carried out for 2017 agricultural season in Babylon /Musaib-Albojasem region 35 km west north of the governorate to evaluate the performance of seven genotypes of rice (Oryza sativa L.) Genetic, environmental and phenotypic variances, heritability percent in the broad sense, genetic and phenotypic Different Coefficients, effect of irrigation methods (flooding and intermittent irrigation) of the genotypes (Amber33, Dijla, Mashkhab 2, Forat, Pernameg4, Yasmin and Ghadir) The research center of the rice in Al-Mashkhab using the experiment of split plots in randomized complete Block design (RCBD) with three replicates. The results can be summarized as follows:The genotypes showed significant differences on the 5% probability level for all studied traits.The genotype Amber 33 superior to all other traits except for the number of effective branches for genotype Forat.The method of irrigation by flooding showed significant superiority of all studied traits.The genetic variance values were higher than the environmental variability values of all traits except for the number of branches.The estimates of heritability values ​​in the broad sense indicated that they were high for all traits.6. The values of the phenotypic and genetic differences were different between low values of the number of days from planting to 50% flowering and medium for the other traits except for the area of the leaf it was high for the irrigation methods and the low of the number of branches. panicle.